2009
DOI: 10.3390/molecules14093142
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis and Antitumor Activity of Amino Acid Ester Derivatives Containing 5-Fluorouracil

Abstract: A series of amino acid ester derivatives containing 5-fluorouracil were synthesized using 1-ethyl-3-(3-dimethylaminopropyl)carbodiimide hydrochloride (EDC·HCl) and N-hydroxybenzotriazole (HOBt) as a coupling agent. The structures of the products were assigned by NMR, MS, IR etc. The in vitro antitumor activity tests against leukaemia HL-60 and liver cancer BEL-7402 indicated that (R)-ethyl 2-(2-(5-fluoro-2,4-dioxo-3,4-dihydropyrimidin-1(2H)-yl)acetamido)-3-(4-hydroxyphenyl) propanoate showed more inhibitory ef… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
11
0

Year Published

2011
2011
2015
2015

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 26 publications
(11 citation statements)
references
References 23 publications
0
11
0
Order By: Relevance
“…Syntheses and studies of 2 and 3: In addition to 5-FU, which is used as drug model, two new 5-FU prodrugs (2 and 3) with two and three 5-FU units, respectively, linked through an ester function to an alkyl core were synthesized ( Figure 3). These linkers can be cleaved chemically or enzymatically [23,24] to generate 5-FU and/or 5-fluorouracil-acetic acid (5-FUA also referred to as compound 1 in this work) whose biological activities are known. [25] Syntheses: Compounds 2 and 3 were prepared as described in Scheme 1.…”
Section: Resultsmentioning
confidence: 99%
“…Syntheses and studies of 2 and 3: In addition to 5-FU, which is used as drug model, two new 5-FU prodrugs (2 and 3) with two and three 5-FU units, respectively, linked through an ester function to an alkyl core were synthesized ( Figure 3). These linkers can be cleaved chemically or enzymatically [23,24] to generate 5-FU and/or 5-fluorouracil-acetic acid (5-FUA also referred to as compound 1 in this work) whose biological activities are known. [25] Syntheses: Compounds 2 and 3 were prepared as described in Scheme 1.…”
Section: Resultsmentioning
confidence: 99%
“…Prior studies have identified that the introduction of an ester function group into the core structure of some plant‐derived anticancer agents such as taxol , camptothecin , bryostatin , and 5‐fluorouracil improved their activity against the usual cell line. Moreover, similar enhancement of the activities is demonstrated in the antiplasmodial and antitrypanosomal activities with bicyclic amides and esters of dialkylamino acids .…”
Section: Resultsmentioning
confidence: 99%
“…These prodrugs are activated by a biological mediator only when get in specific cells or tissues [4]. 5-FU modifications include conjugation with peptides, amino acids, phospholipids and polymers [5][6][7][8][9]. Among 5-FU prodrugs tegafur, carmofur and floxuridine have already proven their clinical efficacy with low toxicity and increased selectivity and metabolic stability [10].…”
Section: Introductionmentioning
confidence: 99%